2016
DOI: 10.1177/2048872616633844
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox disappears in coronary artery bypass graft patients during 20-year follow-up

Abstract: During long-term follow-up the obesity paradox seems to disappear due to progression of cardiometabolic disease in patients who have undergone CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…In contrast to these studies, other studies have not shown an obesity paradox, and their data are summarized in Table . Coutinho and coworkers investigated the association of central obesity expressed by waist circumference and waist to hip ratio compared with BMI on mortality in a review involving 15 923 patients with CAD.…”
Section: Studies Showing No Obesity Paradox In Obese Compared With Nomentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast to these studies, other studies have not shown an obesity paradox, and their data are summarized in Table . Coutinho and coworkers investigated the association of central obesity expressed by waist circumference and waist to hip ratio compared with BMI on mortality in a review involving 15 923 patients with CAD.…”
Section: Studies Showing No Obesity Paradox In Obese Compared With Nomentioning
confidence: 89%
“…The in‐hospital and 1‐year incidence of MACE and all‐cause mortality was similar between the NW, overweight, and obese patients (7.1%, 5.6%, and 5.5%, respectively) for MACE, and (3.3%, 2.4%, and 2.4%, respectively) for all‐cause mortality. Hallberg and colleagues studied the effects of obesity on long‐term survival in 922 patients with CAD undergoing coronary artery bypass grafting. The 10‐year survival was better in the obese (BMI ≥ 30) than the overweight (BMI 25–29.9) and NW (BMI 18.5–24.9) patients.…”
Section: Studies Showing No Obesity Paradox In Obese Compared With Nomentioning
confidence: 99%
“…Some data indicate that mortality was not increased by obesity in the short-term perspective; however, this is associated with an increase in late mortality rates. [19].…”
Section: Discussionmentioning
confidence: 99%
“…15,24,25 Faerri rannsóknir hafa litið á langtímaárangur og niðurstöður þeirra sem birst hafa verið misvísandi hvað árangur varðar. [26][27][28][29] Markmið þessarar rannsóknar var því að varpa ljósi á langtímaárangur sjúklinga með mismikla offitu eftir kransaeðahjáveituaðgerð og bera þá saman við sjúklinga í kjörþyngd. Sérstaklega var litið á langtíma fylgikvilla og langtímalifun auk þess sem sjálfstaeðir forspárþaettir langtímalifunar voru metnir.…”
Section: á G R I Punclassified
“…Svipuðum niðurstöðum hefur verið lýst erlendis. 24,25,27,37 Í heild var 30 daga dánartíðni 2%, og var hún svipuð í öllum LÞS-hópunum. Svipuðum niðurstöðum hefur verið lýst erlendis 28,[37][38][39] , enda þótt til séu rannsóknir sem sýna laegri dánartíðni sjúklinga með háan LÞS.…”
Section: Umraeðurunclassified